2015
DOI: 10.1109/jphotov.2015.2405758
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations and Measured Performance of Nontracked Mirror-Augmented Photovoltaics

Abstract: Costs associated with conventional photovoltaic (PV) installations (module manufacturing, mounts, wiring and installation labor, etc.) scale linearly with system area, and prudent design practices for increasing the light harvesting may significantly enhance the power output per unit area and cost per watt. The use of PV modules that have been augmented by the addition of a solar mirror provides an opportunity to improve light harvesting of a PV module and cost-per-watt considerations if the mirror is less exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the proposed MISPVS, the total solar radiation impinging on the surface of the solar panel (G tp ) is the sum of direct radiation on the solar panel (G dir ), the reflected irradiation (G r ) from the mirror and the total diffuse radiation (G d ) as in (12) [26]. The direct solar irradiation (G dir ), and reflected irradiation from plane mirror (G r ), are obtained from (13) and 14, respectively…”
Section: Integration Of Mirrors In Solar Pv Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the proposed MISPVS, the total solar radiation impinging on the surface of the solar panel (G tp ) is the sum of direct radiation on the solar panel (G dir ), the reflected irradiation (G r ) from the mirror and the total diffuse radiation (G d ) as in (12) [26]. The direct solar irradiation (G dir ), and reflected irradiation from plane mirror (G r ), are obtained from (13) and 14, respectively…”
Section: Integration Of Mirrors In Solar Pv Systemmentioning
confidence: 99%
“…Here, authors observed an enhancement of 26.2% power compared to an equivalent non‐augmented solar PV system [23]. Later, the same authors found that the improvement in power with respect to non‐ augmented PV is only about 12% [13]. Later, the simulation and experimental analysis conducted by Rob W. Andrews et al [32], on the application of plane mirrors on traditional PV system, found a boost in energy about 18%, which indicates that non‐tracked plane mirrors are a low‐cost energy enhancement method for traditional PV system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Solar Durability and Lifetime Extension (SDLE) Research Center at Case Western Reserve University owns and operates a unique outdoor test facility, the "SDLE SunFarm" in Cleveland, OH, 56 that provides 14 dual-axis solar trackers populated with 144 commercial photovoltaic modules, 122 individual grid-connected photovoltaic power plants of varying power, and four mirror-augmented PV (MAPV) modules, 57 with controllable nonuniform irradiance forcing bypass diodes to be forward biased.…”
Section: B Outdoor Studiesmentioning
confidence: 99%